101 facts about horses & ponies - Barnes, Julia, 1955- (Milwaukee, WI : Gareth Stevens Pub., 2002)
An introduction to the history, physical characteristics, behavior, and various breeds of horses and ponies.
Includes bibliographical references (p. ).
Keywords: Horses -- Miscellanea -- Juvenile literature; Ponies -- Miscellanea -- Juvenile literature; Horses; Ponies